Islamism, Muslim Millennials, and Local Political Contestation in Indonesia - Kafid, Nur; Zulkifli, Zulkifli; Hanif, Alimun; Zamhari, Arif (DINIKA : Academic Journal of Islamic Studies, 2021)
There is a trend of increasing Islamism after the 1998 Reformation Era in Indonesia. The previous studies reveal that it is caused, among others, by the weakness of the state, the decline of the authority of moderate Islamic groups, and the use of social media as da’wahchannels by Islamist groups. This studi is qualitative-based research by employing descriptive method and social content analysis of social media. The data were collected through observations (field study) of the election process in the Solo area, from social media, and in-depth interviews with academicians of UIN Surakarta, the initiators, and participants of the LISaN program. This study revealed that the low quality of political education, manipulative information spread on social media, and lack of autonomous political participation by the Muslim millennials have also contributed to the rise of Islamism. Therefore, the Islamic literacy for courteous and tolerant behavior (Literasi Islam Santun dan toleran, LISaN) is necessary to counter the Islamist movement. The LISaN movement which take form a noisy tolerant majority can be a means of values reproduction and encourage individual participation in political and religious affairs, in a polite and tolerant manner.